2005
DOI: 10.1016/j.trstmh.2004.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Oesophagostomum bifurcum-induced nodular pathology in a highly endemic area of Northern Ghana

Abstract: Human infection with Oesophagostomum bifurcum is rare globally, but focally endemic and common in Ghana and Togo. Two clinical presentations are identified: uni-nodular disease, which may be recognized as a 'Dapaong Tumour', and multi-nodular disease. Here, we describe the prevalence of O. bifurcum infection and the association with nodular pathology in northern Ghana. The study was performed in October 2002. Out of a well-defined population of approximately 18000, 928 subjects of all ages were randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Recent studies in humans where nodular pathology and larvae occurred together showed that the chance of developing nodules increased with increasing intensity of infection. Among 928 subjects in a recent study in an endemic zone [41], 44% had O. bifurcum eggs in their stools and 34% had nodular pathology mostly in ascending and transverse colon. Half of them had a multiple nodular pathology detected by ultrasound technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies in humans where nodular pathology and larvae occurred together showed that the chance of developing nodules increased with increasing intensity of infection. Among 928 subjects in a recent study in an endemic zone [41], 44% had O. bifurcum eggs in their stools and 34% had nodular pathology mostly in ascending and transverse colon. Half of them had a multiple nodular pathology detected by ultrasound technique.…”
Section: Discussionmentioning
confidence: 99%
“…in wild apes and those of sanctuaries, however, parasite loads are rarely determined and data obtained by using comparable methods are not available. If a correlation occurs between parasite burden and risk of nodular pathology (as demonstrated in humans [41]), we can suggest that association of mechanical and chemical properties of plants ingested may be used to maintain subclinical level of infection in great apes. Regular ingestion of plants with antihelmintic properties may decrease the number of L3 and adult nematodes in intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Oesophagostomum spp. can be associated with significant pathology because juvenile stages of these parasites encyst during development and cause nodules in the intestinal mucosa, which eventually burst open to release adult forms of the parasite (Huffman et al 1997;Anderson 2000;Huffman & Caton 2001;Storey et al 2001;Acha & Szyfres 2003;Ziem et al 2005;Krief et al 2008). Strongyloides spp.…”
Section: The Model Parasitesmentioning
confidence: 99%
“…14,15 Inhabitants belong to different ethnic groups such as Bimoba, Fulani, Busanga, Kusasi and Maprusi. Surveys on demographics were held annually from June to August, starting from 2002, 16 in which population information including births, deaths and migration was updated. Each year, mouth swabs for DNA analyses were obtained from a subset of adults and newborns.…”
Section: Study Populationmentioning
confidence: 99%